Error Analysis of Learners’ Problem-Solving Abilities in Mathematics Courses: A Newman Error Analysis (NEA) Approach - Ekasari, Aprilita; Putra, Don Jaya (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2024)
This study endeavors to systematically discern the spectrum of learner errors manifesting in problem-solving processes within the domain of mathematics, specifically focusing on the intricacies of integration, utilizing Newman Error Analysis (NEA) as the guiding framework. The cohort under investigation comprises 14 first-year students hailing from the Department of Physics Education at Musamus University, Merauke. Employing a descriptive methodology underscored by a qualitative orientation, this research incorporates tests and interviews as primary instruments for data collection. The tests are designed to meticulously evaluate the array of errors committed by learners, as per the tenets of Newman’s model. Additionally, a subset of four participants is selected for in-depth interviews aimed at elucidating the underlying challenges encountered during problem-solving endeavors, which ultimately contribute to the genesis of learner errors. Analysis of the findings underscores the prevalence of comprehension errors, transformation errors, process errors, and encoding errors amongst learners grappling with problems centered on the subtopic of integration.DOI: 10.17977/jps.v12i12024p044